Pengaruh Kepuasan Kerja, Komitmen Organisasi dan Stres Kerja terhadap Turnover Intention Karyawan BPR (Bank Perkreditan Rakyat) Karanganyar - Erlangga Ekananditya; Riska Fii Ahsani (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
This Research purposes This is analyze significance influence satisfaction work , commitment organization and stress Work to Turnover intention among Regency BPR employees Karanganyar . Type of data used is quantitative data . Data sources used is acquisition of primary data. Sample instudy This as much 50 BPR employees in the Regency Karanganyar . Method used in taking Saturated sampling technique . Determination taking sample fed up done because sample the object under study or data sources are few ( less of 100 people). Technique collection data on study This use observation and questionnaire . Test assumption classic use test: multicollinearity , autocorrelation , heteroscedasticity and normality . The data analysis technique uses a linear regression test double , t test, test F and test R². Results test validity And reliability show that all statement about satisfaction work , commitment organization and stress Work stated valid Because p-value < 0.05 . Results test assumption classic show that all variable has get away test multicollinearity , heteroscedasticity , autocorrelation And normality distribute normal. Results analysis regression obtained equality Y = -4.984 + 0.946 X1 + 0.150 X2 + 0.124 X3 + e. T test results show that satisfaction Work (X₁) has an effect significant to turnover intention , commitment organization (X₂) and stress work (X₃) influential No significant to turnover intention . Results F test is obtained that the regression model used in study This Already appropriate . The R² test results show big donation influence variable independent to dependent as big as the remaining 63.3 % 36.7 % is influenced by other factors outside the model , for example Motivation Work , Leadership Style and others outside study.